Social childcare concept: Social community as a childcare partner for working parents - Kumalasari, Devy; Alhasyimi, Abdul Latif Arifin (University of Muhammadiyah Malang, 2023)
In today's era, it has become easier for working parents to find childcare services because of the growing number of childcare institutions or services. However, limitations in a rural environment requires parents, especially working mothers to find childcare or caregiver substitutes in their social environment. This study aims to describe the concept of social care occurs in rural communities. This exploratory-descriptive qualitative research was carried out in Malang Regency, East Java, using the selected sample and snowball technique. The method used is semistructured interviews conducted with 3 people involved in childcare services for preschool children, and the data analysis model is taken from Miles and Huberman. The research results show that the social care concept has 3 dimensions: the mutually beneficial relationship of social exchange of childcarers and parents; carefree system of child care environment; and co-parenting mechanism. Partnership is performed voluntarily by offering the strategies used to find childcarers by increasing social cohesion in the community and involve children in activities with the social community. This study offers the strategies that can be implemented by working parents in finding childcarers in the social community by prioritizing informal kinship relations.